Tree Preprocessing and Test Outcome Caching for Efficient Hierarchical Delta Debugging - Hodovan, Renata; Kiss, Akos; Gyimothy, Tibor (2017 IEEE/ACM 12th International Workshop on Automation of Software Testing (AST), 2017)
Test case reduction has been automated since the introduction of the minimizing Delta Debugging algorithm, but improving the efficiency of reduction is still the focus of research. This paper focuses on Hierarchical Delta Debugging, already an improvement over the original technique, and describes how its input tree and caching approach can be changed for higher efficiency. The proposed optimizations were evaluated on artificial and real test cases of 6 different input formats, and achieved an average 45% drop in the number of testing steps needed to reach the minimized results - with the best improvement being as high as 82%, giving a more than 5-fold speedup.